2016
DOI: 10.1051/0004-6361/201527517
|View full text |Cite
|
Sign up to set email alerts
|

Red supergiants and the past of Cygnus OB2

Abstract: Context. Red supergiants are the evolved descendants of massive stars with initial masses between 7 and 40 M . Their brightness makes them easily detectable in the near infrared, making them useful probes of star formation that occurred several tens of Myr ago. Aims. We investigate the past star formation history of Cygnus OB2, the nearest very massive OB association, using red supergiants as a probe. Our aim is to confirm the evidence, found by previous studies, that star formation in the Cygnus OB2 region st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…The association, which formed massive stars over an extended period lasting from ∼ 30 Myr to ∼ 10 Myr ago, may have hosted several tens of O stars and the precursors of around one hundred supernovae up to the present time. Such an extended period of star formation may not be an anomalous feature of large, rich OB associations, based on similar recent findings on the younger, more nearby Cygnus OB2 association (Hanson 2003;Comerón & Pasquali 2012;Comerón et al 2016;Berlanas et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…The association, which formed massive stars over an extended period lasting from ∼ 30 Myr to ∼ 10 Myr ago, may have hosted several tens of O stars and the precursors of around one hundred supernovae up to the present time. Such an extended period of star formation may not be an anomalous feature of large, rich OB associations, based on similar recent findings on the younger, more nearby Cygnus OB2 association (Hanson 2003;Comerón & Pasquali 2012;Comerón et al 2016;Berlanas et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…They found no signs of dynamical evolution of Cyg OB2 which is inconsistent with the idea that all stars form in dense, compact clusters. On the other hand, Comerón et al (2016) investigated the past star formation history of Cygnus OB2 using the red supergiants detectable in the near infrared as a probe to trace massive stars with initial masses between 7 and 40 M ⊙ . They concluded that Cygnus OB2 has a history of star formation extending into the past for at least 20 Myr.…”
Section: Cosmic Rays In Superbubblesmentioning
confidence: 99%
“…But only a fraction <1/3 of the SN II come from the prominent O-stars all of which explode by the first ~13 Myr of an OB association's life, leaving all of the remaining SN II progenitors uncounted in the surveys of OB associations which are based only on the O-star counts. Recently, however, (Comeron et al 2016) has successfully surveyed the early B-star Red supergiants in the Cygnus OB2 association significantly increasing the potential CCSN count in that association and since these are roughly half of the cosmic ray sources more such surveys need to be made.…”
Section: Summary and Further Workmentioning
confidence: 99%